Theoretical analysis of the magnetic circular dichroism in the 2p3d and 2p4d x-ray emission of Gd - Groot, F.M.F. de; Nakazawa, M.; Kotani, A.; Krisch, M.H.; Sette, F. (The American Physical Society, 1997)
The 2p3d and 2p4d x-ray emission spectral shapes have been calculated using a theoretical description of spin-polarized 2p photoemission and atomic multiplet calculations of the 2p3d and 2p4d radiative decay. Emphasis is given to the use of circular-polarized x rays for the excitation process. Good agreement with experiment is found and all visible experimental structures can be explained. It is shown that because of weak multiplet effects in the intermediate state, it is possible to use the incoherent, two-step model. The angle between the emitted x rays and the magnetization is able to affect the magnetic circular dichroism (MCD) spectral shape observed, while the angle between the incident x ray and the magnetization only affects the intensity of the MCD.
Keywords: Natuur- en Sterrenkunde